Phenomenology Study of Nutrition Support in Children with Acute Lymphoblastic Leukemia during Chemotherapy - Dian Estiningtyas; Bhisma Murti; Hermanu Joebagio (Journal of Maternal and Child Health, 2020)
Background: Acute lymphoblastic leukemia in children is a case most often found in children under 15 years with a percentage of 30-40%. According to data from the medical record installation of Dr. Kariadi Hospital, the number of children under 15 years old with LLA hospitalized during 2015 - 2019 was 526 cases with a death rate of 69 patients. The treatment process is quite complex because it takes a long time and requires active involvement between health workers and parents. This study aims to describe the nutritional support of children with Acute Lymphoblastic Leukemia (ALL) during the chemotherapy process in SemarangSubjects and Method: This was a qualitative study with a phenomenological perspective. The study was conducted at Dr. Kariadi Hos